Efektivitas Penggunaan Media Paper Toys dalam Meningkatkan Kemampuan Motorik Halus bagi Anak Gangguan Spketrum Autisme - Padina, Intan; Irdamurni, Irdamurni (Jurnal Penelitian Pendidikan Khusus, 2021)
This research was motivated by the problems that researchers encountered in a child with Autism Spectrum Disorder (Autism Spectrum Disorder) who experienced fine motor barriers, especially in folding paper and gluing paper using glue. This study aims to improve children's fine motor skills, especially in folding and pasting paper using Paper Toys media. This study uses a quantitative research experimental method with a Single Subject Research (SSR) approach with an A-B-A design. Based on the results of data acquisition, it can be concluded that using Paper Toys media can improve children's fine motor skills (folding and pasting paper) for children with Autism Spectrum Disorder (ASD).